Linking Leadership Styles and Employees Retention: The Mediating Role of Job Satisfaction - ABDELHAMIED Hany Hosny; ALAZHAR Tahar Ayed; HAMZA Amani Mohamed (Communications of International Proceedings, 2023)
Numerous studies have shown the benefits and importance of leadership styles in the service sector, and their role in enhancing employees’ overall well-being and retaining qualified capital. This study was designed to test the link among the different styles of leadership, job satisfaction and employees' retention. A total of (606) questionnaires were distributed to the employees in different hotels in Saudi Arabia. Structural Equation Modelling (PLS smart) was used for assessing the fit of the model. The findings indicated that leadership styles showed a high level of job satisfaction among hotel staff. A positive relationship was found between the overall score for servant leadership style and job satisfaction (r = 0.484**). The overall empowering leadership score correlated positively with job satisfaction (r = 0.591**). The same result was repeated when examining the link between authentic and job satisfaction. Among the leadership styles measured, only servant and empowering are associated directly to retention, however authentic leadership does not directly affect employee retention. The results also clarified that job satisfaction is a strong predictor for the employee’s retention with the different leadership styles. The managerial implications, study limitation and suggestion for further study were also discussed.
Keywords: Leadership styles; Job satisfaction; employees’ retention; hospitality industry; Saudi Arabia.